Cooperative MIMO communications in wireless sensor networks: Energy efficient cooperative MAC protocol - Ahmad, Mohd Riduan; Dutkiewicz, Eryk (Penerbit Universiti Teknikal Malaysia Melaka, 2009)
Multiple sensor nodes can be used to transmit and receive cooperatively and such a configuration is known as a cooperative Multiple-Input Multiple-Output (MIMO) system. Cooperative MIMO systems have been proven to reduce both transmission energy and latency in Wireless Sensor Networks (WSNs). However, most current work in WSNs considers only the energy cost for the data transmission component and neglects the energy component responsible for establishing a cooperative mechanism. In this work, both transmission and circuit energies for both components are included in the performance models. Furthermore, in previous work, all sensor nodes are assumed to be always on which could lead to a shorter lifetime due to energy wastage caused by idle listening and overhearing. Low duty cycle MAC protocols have been proposed to tackle this challenge for non- cooperative systems. Also in this work, we propose a new cooperative low duty cycle MAC protocol (CMAC) for two cooperative MIMO schemes: Beamforming (CMACBF) and Spatial Multiplexing (CMACSM). Performance of the proposed CMAC protocol is evaluated in terms of total energy consumption and packet latency for both synchronous and asynchronous scenarios. All the required energy components are taken into consideration in the system performance modeling and a periodic monitoring application model is used. The impact of the clock jitter, the check interval and the number of cooperative nodes on the total energy consumption and latency is investigated. The CMACBF protocol with two transmit nodes is suggested as the optimal scheme when operating at the 250 ms check interval with the clock jitter difference below 0.6Tb where Tb is the bit period corresponding to the system bit rate.